2021
DOI: 10.3390/membranes11060411
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Extracellular Vesicles: Current Findings, Challenges, and Future Applications

Abstract: In recent years, plant-derived extracellular vesicles (PDEVs) have gained the interest of many experts in fields such as microbiology and immunology, and research in this field has exponentially increased. These nano-sized particles have provided researchers with a number of interesting findings, making their application in human health and disease very promising. Both in vitro and in vivo experiments have shown that PDEVs can exhibit a multitude of effects, suggesting that these vesicles may have many potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 46 publications
0
45
0
Order By: Relevance
“…Accarie et al showed that intravenously injection of human mesenchymal stem cells-derived EVs protected the intestinal epithelium's integrity in a mouse model of acute radiation syndrome ( 22 ). Lately, the utility of plant-derived EVs in therapeutic drugs has also gained substantial interest ( 23 , 24 ). Hence, we intended to isolate EVs from M. charantia that its extract polysaccharide had neuroprotective effects against cerebral ischemia/reperfusion injury via scavenging excessive free radicals ( 9 ) and enhancing neural stem cells proliferation ( 10 ) and differentiation ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accarie et al showed that intravenously injection of human mesenchymal stem cells-derived EVs protected the intestinal epithelium's integrity in a mouse model of acute radiation syndrome ( 22 ). Lately, the utility of plant-derived EVs in therapeutic drugs has also gained substantial interest ( 23 , 24 ). Hence, we intended to isolate EVs from M. charantia that its extract polysaccharide had neuroprotective effects against cerebral ischemia/reperfusion injury via scavenging excessive free radicals ( 9 ) and enhancing neural stem cells proliferation ( 10 ) and differentiation ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid composition of P-EVs is different from that of EVs extracted from animal cells. However, the study of the lipid composition of P-EVs has become attractive since it has been shown that they can interact with and internalize by animal cells [ 85 ]. Therefore, the composition of lipids has a direct impact on the biological function of P-EVs [ 47 ].…”
Section: Biological Composition and Function Of P-evsmentioning
confidence: 99%
“…EVs derived from non-toxic plants can eliminate the problems associated with existing nanosized delivery systems due to their natural composition, origin, and opportunity to extract them in bulk from economical plant sources [ 85 ] (Fig. 4 ).…”
Section: Therapeutic Application Of P-evsmentioning
confidence: 99%
“…A growing interest is also arising from the study and exploitation of EVs or, more in general, of micro- and nano-sized vesicles, derived from non-human sources, such as bacteria ( Bitto and Kaparakis-Liaskos, 2017 ), bovine milk ( Kleinjan et al, 2021 ; Samuel et al, 2021 ), and edible plants ( Wang et al, 2014 ; Raimondo et al, 2015 ; Bokka et al, 2020 ; Stanly et al, 2020 ; Raimondo et al, 2021 ). In particular, plant-derived vesicles are currently considered as biocompatible, sustainable, green, next-generation nanocarriers ( Kameli et al, 2021 ; Urzì et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%